Health sciences libraries and public health education awareness in social media platforms (Journal of EAHIL, 2017)
Information sciences in the current social media age cannot be thought of separately from social media platforms. The most popular of these platforms are Facebook and Twitter with regard to free and easy access and use. How can health sciences libraries and medical librarians help the users reach information services using these social media? The principal argument is that academic health sciences libraries should support their users by invoking public health education in social media platforms such as Facebook and Twitter. The Koç University School of Nursing Library’s objective is to use Facebook's insight attribute in order to evaluate how many people can reach public health education information using social media. In order to develop our argument, the methodology was defined by analysing our goals and metrics. This study focused on subject titles such as: injections, breast cancer, diabetics, first aid, hypertension, air pollution, infectious diseases, tuberculosis, quit smoking, cervical cancer, birth control, AIDS, etc. and content management tools such as like, share, timeline, photo post. The aim of this analysis was to discuss how medical libraries can use social media efficiently.